Letter regarding Zhao et al. entitled "DPYD gene polymorphisms are associated with risk and chemotherapy prognosis in pediatric patients with acute lymphoblastic leukemia". Issue 6 (May 2017) - Deenen, Maarten J; Henricks, Linda M; Sonke, Gabe S; Schellens, Jan HM; Meulendijks, Didier
Zhao et al. investigated the association between germline genetic polymorphisms in DPYD, the gene encoding dihydropyrimidine dehydrogenase, and (1) the risk of developing pediatric acute lymphoblastic leukemia and (2) outcome of acute lymphoblastic leukemia following the treatment with 5-fluorouracil plus oxaliplatin (FOLFOX). The authors found that the common DPYD variant c.85T>C (rs1801265, DPYD *9A) was significantly associated with (1) risk of developing pediatric acute lymphoblastic leukemia, (2) complete response rate, (3) event-free survival, and (4) treatment-related toxicity. The authors conclude that patients carrying the c.85T>C C allele have an increased risk of developing acute lymphoblastic leukemia and have inferior outcome, and that DPYD c.85T>C can be used as a guide for individualized treatment and the decision to utilize 5-fluorouracil in acute lymphoblastic leukemia patients. In our view, the published article gives rise to multiple critical issues regarding the study's rationale and the methodology used, which strongly question the validity of the authors' conclusions.